0141 Mediating effects of health on the association between negative life events in childhood on future labour market participation. A 7-year follow-up study. (23rd June 2014) - Labriola, Merete; Hviid Andersen, Johan; Lund, Thomas
Abstract : Objectives: The aim of this study was to investigate if effects of multiple negative life events in childhood on future labour market participation were mediated through 3 measures of mental, general, and psychosomatic health. Method: Of a cohort of 3681 born in 1989 in the county of Ringkjoebing, Denmark, 3058 (83%) completed a questionnaire in 2004. They were followed in a register on social benefits for 12 months in 2010–2011. Logistic regression analyses were used to investigate associations between negative life events in early childhood and future labour market participation at age 21–22. Sobel-Goodman test for mediating effects was used to determine, if part of the effects were mediated through mental, general and psychosomatic health at age 14/15. Results: Labour market participation decreased with increase in negative life events, especially for females. However, for females, only a small proportion of this effect was mediated through health: 1% through psychosomatic symptoms, 4% through general self-rated health, and 4% through mental health. For males, a larger proportion of the effects were mediated through health: 1% through psychosomatic symptoms, 8% through general self-rated health, and 14% through mental health. Conclusions: Information on childhood conditions may increase the understanding of determinants of labour market participation for young adults. Only a small proportion of the negative effects of childhood adversities were mediated through health among females. For males, the results suggest that childhood adversities affect especially mental health to a degree where it threatens future labour market status.